Development of Teaching Materials Assisted by the Kvisoft Flipbook Maker Application to Improve Students Critical Thinking Skills - Muhammadi Muhammadi; Niki Yulianti (Postgraduate, University of Mataram, 2023)
The PBL approach must be used in the creation of instructional materials for class III primary schools, utilizing the Kvisoft Flipbook Maker application. This study employs a new design for development research, or R&D, which proceeds through the following processes to arrive at the ADDIE model: analysis, design, development, implementation, and evaluation. Students in class III at SDN 01 Campago, SDN 03 Limo Badak, and SDN 10 Sasai Kandang in the Malalak District of the Agam Regency served as the research subjects. The results obtained from the standard validity analysis were